Pursuing equity through transformative mixed methods Research: The case of secondary transition - E. Kutscher; W. Zeng; K. Reardon; S.L. McDaniel; V.L. Mazzotti (Methods in Psychology)
This study examines how mixed methods research within secondary transition reflects transformative values. We develop nine guiding questions based on established transformative criteria (Sweetman et al., 2010) and transition literature (Scott and Shogren, 2023; Trainor et al., 2020; Trainor and Romano, 2023). We apply the guiding questions to investigate how 22 mixed methods studies enhanced equity and quality of life for transition-age disabled youth. Findings provide insights into how researchers are applying transformative approaches to promote equity and improved quality of life, as well as opportunities for advancing the application of transformative worldviews.